Optimalisasi Prediksi Penjualan Produk Herbal Menggunakan Metode Monte Carlo dalam Meningkatkan Transaksi - Nova Hayati (SAFE-Network, 2020)
Herbs are a product that is in great demand by the public. With so many enthusiasts of herbal products, there is a need for product availability to increase sales transactions for these products. To increase sales transactions for these products, one process that can be done is to predict the sales of herbal products, with data used from January 2018 to December 2019 at the An Nabawi herbal shop. The prediction process is carried out using the Monte Carlo method and to simplify the prediction process a web-based system with the PHP programming language is implemented to make it easier. With the Monte Carlo method used in this study to predict sales of herbal products so that the leadership can use it to make decisions on the availability of herbal products in the shop. The sales prediction results obtained from the Monte Carlo simulation process with an accuracy rate of 87.91%. In this way, the Monte Carlo method can be applied to predict the future sales of herbal products and can be used by store leaders to make decisions regarding the availability of herbal products.